2020
DOI: 10.1021/acssuschemeng.0c00734
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of Using Calcium Silicate Carbonation to Synthesize High-Performance and Low-Carbon Cements

Abstract: Cement is the world’s most widely consumed man-made material and it contributes between 5% and 10% of the total annual anthropogenic CO2 emissions. Here, we report on a new method for producing crystalline calcium silicate hydrate (CCSH) phases with low lifecycle carbon emissions. The materials were made by curing silicate feedstocks, principally pseudowollastonite (CaSiO3), under elevated partial pressures of CO2 in buffered aqueous solutions. CCSH mortars cured for 7 days achieved compressive strength of 13.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 20 publications
(35 reference statements)
1
5
0
Order By: Relevance
“…Akin results were reported in Refs . While calcite has different morphologies, , only pillar-like (or scalenohedral-rhombohedral) calcite in different sizes was detected in our samples after carbonation (Figure c,e).…”
Section: Results and Discusionsupporting
confidence: 81%
“…Akin results were reported in Refs . While calcite has different morphologies, , only pillar-like (or scalenohedral-rhombohedral) calcite in different sizes was detected in our samples after carbonation (Figure c,e).…”
Section: Results and Discusionsupporting
confidence: 81%
“…Lime mortar is typically prepared by mixing hydrated lime powder (Ca(OH) 2 , portlandite) with water and allowing the paste to carbonate in air. While this process is more sustainable than the use of Portland cementsince atmospheric CO 2 is sequestered while the mortar carbonates 51 mortar carbonation is slow (i.e., months to years). Further, incomplete carbonation leaves unreacted Ca(OH) 2 within substrates, which can produce high pH conditions that could be harmful to corals.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Research exploring tobermorite synthesis from calcium silicates and calcium aluminum silicates has demonstrated that alkaline solutions are required for precipitation. ,,, Sodium bases, such as NaOH, have been shown to facilitate the precipitation of tobermorite better than other alkali metals. , Tobermorite precipitation from calcium silicates has also been described as the crystallization of CSH gel. , The formation of tobermorite and other CCSH phases from pseudowollastonite has been shown to increase when exposed to both sodium and CO 2 ; CCSH phases have precipitated when the carbon is delivered as a salt, for example, as Na 2 CO 3 or NaHCO 3 or CO 2 gas and NaOH. However, the effects of CO 2 and sodium concentrations on the amount and phases of precipitated CCSH have not been explored in detail. Prior work in our laboratory suggested that the crystal structure and dissolution characteristics of the parent silicate were a major factor impacting CCSH precipitation .…”
Section: Introductionmentioning
confidence: 99%
“…A large body of literature explores mix designs and curing techniques that incorporate waste slags and ashes to further improve OPC hydration. The waste products can improve the compressive strength and other properties by increasing the formation of calcium silicate hydrate (CSH) gel, the key reaction product of OPC hydration . These materials are rich in calcium silicates, which are generally not hydraulically activated, like OPC, but they can be reacted to form cementitious materials on their own using alkali or temperature activation. As one example, the calcium silicate pseudowollastonite (α-CaSiO 3 ) can be carbonated in alkaline conditions and elevated temperatures to produce crystalline calcium silicate hydrate (CCSH) phases alongside calcium carbonates. …”
Section: Introductionmentioning
confidence: 99%